Unaccompanied Young Migrants : Identity, Care and Justice - Willis, Katie, 1968-; Gupta, Anna; Clayton, Sue (Book collections on Project MUSE., 2019)
Exploring in depth the journeys migrant youth take through the UK legal and care systems, this book contributes new thinking, from a social justice perspective, on migration and human rights for policy, practice and future research.